Design of Catamaran Ship as Inland Waterways Transportation Mode in Samarinda - Alamsyah Alam; Muhammad Dipo Nugroho (Badan Riset dan Inovasi Nasional, 2018)
At the end of 2016 public transport had only reached urban area of Samarinda, and it has not yet accessed the outskirt area of Samarinda. The lack of transportation connecting communities from each region is a problem. The purpose of this research was to design the inland waterways tranportation mode in the out skirt city of Samarinda. The used method was the trend curve and optimization approach. The results showed the principal dimension of ships had lenght over all (Loa) = 12.7 meters, draft (T) = 0.53 meters, the breadth of each hull (B) = 1.3 meters, the total breadth (BT) = 5.5 meters and height (H) = 1.6 meters, Cb = 0.54, Vs = 10 knots, Crew = 4 person, passenger = 36 person.